2021
DOI: 10.1051/shsconf/20219206001
|View full text |Cite
|
Sign up to set email alerts
|

Dual quality and its influence on consumer behaviour according to the income

Abstract: Research background: Dual quality occurred in natural way after fall of Communism. Global producers from Western countries had to adapt formulas and composition of their products to living standards in countries of former soviet bloc. Purpose of the article: But present situation is different, living standards equalize, people travel, they purposely buy abroad, and they discover that international goods known from home shops have different attributes – composition, colour, aroma or density of product – in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…But Ezenyilimba and Akpan (2019) examined the effect of income on the buying behaviour of online shoppers in Nigeria and the findings revealed that income has significant effect on buying behaviour of online shoppers in Nigeria. Other syduies that established a relationship between income and consumer behaviour also are Valaskova, Durana and Adamko (2021), Alghanim and Ndubisi ( 2022), Wang, An, Gao, Kiprop and Geng (2020), Matos, Vieira, Bonfanti and Mette (2019), Astuti, Anggreni, Khairani, Nasriandani, Alfiona, Putri and Asyari (2022), Shi, Chen, Li, Ma and Liu (2021) and Bartkova and Sirotiaková (2021). Thus, this study argued that income could positively influence consumer behaviour of foreign rice consumers in Northern Nigeria…”
Section: Income and Consumer Behaviourmentioning
confidence: 99%
“…But Ezenyilimba and Akpan (2019) examined the effect of income on the buying behaviour of online shoppers in Nigeria and the findings revealed that income has significant effect on buying behaviour of online shoppers in Nigeria. Other syduies that established a relationship between income and consumer behaviour also are Valaskova, Durana and Adamko (2021), Alghanim and Ndubisi ( 2022), Wang, An, Gao, Kiprop and Geng (2020), Matos, Vieira, Bonfanti and Mette (2019), Astuti, Anggreni, Khairani, Nasriandani, Alfiona, Putri and Asyari (2022), Shi, Chen, Li, Ma and Liu (2021) and Bartkova and Sirotiaková (2021). Thus, this study argued that income could positively influence consumer behaviour of foreign rice consumers in Northern Nigeria…”
Section: Income and Consumer Behaviourmentioning
confidence: 99%
“…Bartkova and Sirotiaková (2021) investigated the dual quality and its influence on consumer behaviour according to income. The research used primary data.…”
mentioning
confidence: 99%